The Study of the Rusunawa Children's Playroom in BNI Trembesi Park - Cut Nur Hidayati; Irin Caisarina (Jurnal RAUT, 2023)
The Child Friendly Playroom (RBRA) is a place that can accommodate children's play activities safely and comfortably for the optimal and comprehensive sustainability of children's growth and development. The availability of appropriate facilities and infrastructure for the growth and development of children in Rusunawa is part of providing child-friendly Rusunawa. The study of the Rusunawa Keudah Children's Playroom at the BNI Trembesi Park is useful for early identification of a Child Friendly Playroom. The research method used is descriptive qualitative by analyzing, describing, concluding the data until finally obtaining the depth of information as a knowledge of the research subject. Observations are seen in the elements of the Child-Friendly Playroom such as: Comfort, security and safety, Child-friendly accessibility, Health, Environment and Green Open Space, Supporting facilities and infrastructure. The results of the Study on the Children's Playroom of Rusunawa Keudah at the BNI Trembesi Park by seeing that all of them still do not meet the elements of a child-friendly playroom and it is necessary to evaluate and develop a playroom at the BNI Rusunawa Keudah Transplantation Park both inside and outside the playroom.